Design of an experimental device for the measurement of the coefficient of restitution - Borsa, Eugenia (2019)
In this work an experimental device was designed and built to measure the coefficient of restitution of particles of different type and size. The aim of the study is to analyze the dependence of the coefficient of restitution with the impact velocity, the shape and mass of the particles. Three types of particles of different origin and shape were used: lentils, urea granules and polyethylene pellets. Besides, two impact materials were evaluated: steel and polycarbonate. The images were captured with a high resolution camera, recording the moment at which the particles impact and bounce on the surface. Image processing software was used to obtain the position of the particle at the instants before and after the impact. The particle velocities before and after the collision were calculated and the coefficient of restitution of the particles were obtained. The experimental results showed the dependence of the coefficient of restitution with the studied variables, providing useful information about the energy dissipation for numerical simulations and a breakthrough in the study of gas-solid flow systems.